MODEL PENDUGAAN PRODUKSI GONDORUKEM DI DAERAH JAWA TENGAH - Suwidji Basuki; Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Total area of Pine forests at Perum Perhutani Unit I, Central Java, relatively enlarges each year, but its utilization for wood and resin tapping are only 60%. Pine resin processing of collophonium commodity has yielded 65% in volume. This study showed a predictive model of collophonium production at Central Java as Y = -11,32+0,65X1**-0,43X2 +0,14X3*The model above showed that Pine resin volume (X1) is highly significant and collophonium price (X3) is significant to collophoniutn production (Y), whereas labour variable (X2) is not significant because the ultilization of labour is not efficient yet. The simple regressions Y1 = 28,77 + 0,65 X1 and Y2 = 1075 + 9,35 X3 are used to explain the relation between Y and X1 or X2 individually.